Efektifitas Kepemimpinan Kepala Madrasah dalam Meningkatkan Prestasi Siswa di MI Ma’arif Kaliwiro Tahun Pelajaran 2023/2024 - Kiyatun Kiyatun; Muchotob Hamzah; Ngarifin Shidiq (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of this research is to collect data on education in general and the leadership style of the madrasah principal in particular in an effort to improve student achievement. This research method is qualitative. Research conducted on descriptive analysis, speech, writing, and behavior as reported by individuals (subjects) themselves is known as qualitative research. The subjective nature of the principal is emphasized in this research approach. In order to increase the number of student achievements at MI Ma'arif Kaliwiro, the Madrasah principal's leadership plan includes involving and maximizing stakeholders, parents and students, conducting supervision, setting annual achievement targets, and giving gifts. Setting an example to the community, implementing strategic reforms with circumstances, and utilizing a combination of authoritarian and democratic leadership styles based on circumstances, and formulating the Madrasah's vision and mission to meet the aspirations of the community, parents, and Madrasah residents are part of the Madrasah principal's leadership strategy at MI Ma'arif Kaliwiro.